APLIKASI MODEL STATISTIKA INFERENSIA DALAM PEMBELAJARAN MATEMATIKA EKONOMI - Rahmattullah (Program Studi Pendidikan Matematika, STKIP Bina Bangsa Getsempena, 2019)
This study aims to observe the application of inferencing statistical models in economic mathematics learning. The data used are panel data consisting of 6 zones, namely the central, north, east, southeast, south and west zones in the Aceh Province in 2010-2016. The method used is panel data regression with the selection between the Commond Pool Model, Fixed Effect Model or Random Effect Model. The results obtained from the three models are pool, fixed and commond effect that the fixed effect model is quite good in explaining the economic growth of strategic areas in Aceh Province. Another important finding in this study is the Human Development Index (HDI) does not affect economic growth both in conditions of intra and inter-zone development disparities. Abstrak Penelitian ini bertujuan untuk mengamati aplikasi model statistika inferensia dalam pembelajaran matematika ekonomi. Data yang digunakan adalah data panel yang terdiri dari 6 zona yaitu zona pusat, utara, timur, tenggara, selatan dan barat di Provinsi Aceh tahun 2010-2016. Metode yang dipakai adalah regresi data panel dengan pemilihan diantara Pool Commond Model, Fixed Effect Model atau Random Effect Model. Hasil yang diperoleh menunjukkan dari ketiga model yaitu pool, fixed dan commond effect bahwa model fixed effect cukup baik dalam menjelaskan pertumbuhan ekonomi kawasan strategis di Provinsi Aceh. Temuan penting lain dalam penelitian ini adalah Indek Pembangunan Manusia (IPM) tidak menpengaruhi pertumbuhan ekonomi baik dalam kondisi kesenjangan pembangunan intra maupun antar zona. Kata kunci: Commond Pool Model, Fixed Effect Model, Random Effect Model